Os discursos verbais e iconográficos sobre os negros em livros didáticos de história - Joao Bernardo da Silva Filho (2005)
This thesis has as object the analysis of the verbal and iconographic discourse about black people in a History textbook, carried through in three editions PILETTI, Nelson. História do Brasil. São Paulo: Ática, 1986; PILETTI, Nelson; PILETTI, Claudino. História & vida. Brasil: da Pré-História à Independência. v.1. São Paulo: Ática, 1997; and PILETTI, Nelson; PILETTI, Claudino. História & vida integrada. 7ª série. São Paulo: Ática, 2001 , widely adopted in Basic Education Schools, two of them, evaluated by the Programa Nacional do Livro Didático (National Program of School Textbooks PNLD). The inquiry tries to answer, basically, to only one question: which history do the textbooks, pretty much used by the teachers in classroom, tell about black people in the conformation of the national history? After a sociopolitical and cultural contextualization of the verbal and iconographic discourse in textbooks and the presentation of organization aspects of three editions, it had been analyzed, in each volume, texts, images and activities which were elaborated for the pupils. In order to reach the considered objectives, this work tries to find a theoretical referential that deals with the knowledge of representation, power and imaginary, in special, the concepts formulated by Michel De Certeau and Roger Chartier, which made possible to understand that the reconstruction of the facts by the verbal and iconographic discourses is embodied by the definition of representations that are a result of concrete and imaginary interests. This referential was also important to the understanding of the textbook specificities, with sights to establish relations between the verbal and iconographic discourses constructed on black people and the ideological, historiographical, and methodological presuppositions that had supported the authorship in the production of the selected school manuals.